Perancangan Sistem Informasi Perpustakaan SMK Negeri 1 Merdeka Berastagi Berbasis web Menggunakan TOGAF ADM - Barus, Ananda Br; Ikhwan, Ali (STMIK Banjarbaru, 2025)
The development of information technology encourages educational organizations to manage data more efficiently, including school libraries. Manual management at the SMK Negeri 1 Merdeka Berastagi Library causes slow data retrieval, the risk of archive loss, and late reporting. This study aims to design a blueprint for a web-based library information system architecture using the TOGAF ADM (Architecture Development Method) framework. This approach focuses on strategic planning, including the Preliminary phase, Architecture Vision, Business Architecture, Information System Architecture, Technology Architecture, Opportunities & Solutions, Migration Planning, and Architecture Change Management. The results show that TOGAF ADM produces a business, data, application, and technology architecture design that aligns with school needs, and provides a migration roadmap towards an integrated information system. This study emphasizes the importance of strategic planning as a foundation for system development, while offering novelty in the form of the application of TOGAF ADM specifically in the context of vocational high school libraries, which has previously been rarely studied.Keywords: TOGAF ADM; Library Information System; Enterprise Architecture; Strategic Planning.AbstrakPerkembangan teknologi informasi mendorong organisasi pendidikan untuk mengelola data secara lebih efisien, termasuk perpustakaan sekolah. Pengelolaan manual pada Perpustakaan SMK Negeri 1 Merdeka Berastagi menyebabkan lambatnya pencarian data, risiko kehilangan arsip, serta keterlambatan laporan. Penelitian ini bertujuan merancang blueprint arsitektur sistem informasi perpustakaan berbasis web dengan menggunakan kerangka kerja TOGAF ADM (Architecture Development Method). Pendekatan ini berfokus pada perencanaan strategis, meliputi fase Preliminary, Architecture Vision, Business Architecture, Information System Architecture, Technology Architecture, Opportunities & Solutions, Migration Planning, serta Architecture Change Management. Hasil penelitian menunjukkan bahwa TOGAF ADM menghasilkan rancangan arsitektur bisnis, data, aplikasi, dan teknologi yang selaras dengan kebutuhan sekolah, serta memberikan roadmap migrasi menuju sistem informasi yang terintegrasi. Penelitian ini menekankan pentingnya perencanaan strategis sebagai fondasi pengembangan sistem, sekaligus menawarkan novelty berupa penerapan TOGAF ADM khusus di konteks perpustakaan SMK, yang sebelumnya masih jarang diteliti.